2015
DOI: 10.1111/sum.12220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crop residue returns on N2O emissions from red soil in China

Abstract: For a long time, farmers in the red soil region of southern China have returned crop residues to the soil, but how various crop residues influence nitrous oxide (N 2 O) emissions is not well understood. We compared the influence of returning different crop residues [rapeseed cake (RC), maize straw, rice straw and wheat straw (WS)] in combination with different levels of nitrogen (N) fertilizer (nil, low and high) on red soil N 2 O emissions. Results confirmed the inverse relationship between cumulative N 2 O e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
1
5
0
2
Order By: Relevance
“…The influence of C on denitrification occurs with both the provision of C to denitrifying bacteria and the stimulation of microbial metabolism, which increases consumption, creating favourable conditions for denitrification. Wu et al () also observed an inverse relation between N 2 O fluxes and the biomass C/N ratio on different cover crops, confirming our findings. Meurer et al () verified that the formation of stable microaggregates and the adhesion of fine soil particles and iron oxides create a soil structure that provides better drainage and greater aerobiosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The influence of C on denitrification occurs with both the provision of C to denitrifying bacteria and the stimulation of microbial metabolism, which increases consumption, creating favourable conditions for denitrification. Wu et al () also observed an inverse relation between N 2 O fluxes and the biomass C/N ratio on different cover crops, confirming our findings. Meurer et al () verified that the formation of stable microaggregates and the adhesion of fine soil particles and iron oxides create a soil structure that provides better drainage and greater aerobiosis.…”
Section: Discussionsupporting
confidence: 92%
“…Kong et al () showed that the application of synthetic N fertilizer causes the fastest N turnover and greater incorporation of fertilizer‐N into the less stable silt‐and‐clay fraction, but also the largest N 2 O fluxes among the three cropping systems. The interactions between SOM and N 2 O emissions usually result from a larger proportion of labile fractions in SOM, with a large supply of residue‐derived N (Wu et al, ). In addition, the strong organo–mineral interaction of mineralized SOM fractions, which is predominant in the weathered soils of tropical regions, can contribute to SOM stabilization and explain the reduced N 2 O emissions from savanna soils under natural vegetation (Santos et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study (e.g., Abagandura et al., 2019b) also reported that grazing CCs for ∼1 mo did not affect cumulative N 2 O flux vs. ungrazed CC. However, significantly higher cumulative N 2 O flux in LdC+G than in the GdC+G at this site may be due to higher N concentration of legume residue that decompose rapidly and release N 2 O. Mineralization of crop residues and flux of N 2 O is dependent on C:N ratio of the residues (Wu, Lin, Liu, Wan, & Hu, 2016). The legume‐based plant residues having a narrow C:N ratio and high N content generally result in rapid N mineralization and particularly higher N 2 O flux vs. residues having high C:N ratio (Li, Sørensen, Olesen, & Petersen, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…However, other studies observed the opposite effect on soil N 2 O emissions after residue amendment [12,13,33]. According to the results of Wu et al [34], the residue C/N ratio is a good predictor of soil N 2 O emissions. Chen et al [9] reported that residue amendment generated significantly positive effects on soil N 2 O emissions when C/N ratios of crop residues were <45, slightly positive effects for C/N ratios of 45-100, and slightly negative effects for C/N ratios >100.…”
Section: N 2 O Emissionsmentioning
confidence: 95%
“…Chen et al [9] reported that residue amendment generated significantly positive effects on soil N 2 O emissions when C/N ratios of crop residues were <45, slightly positive effects for C/N ratios of 45-100, and slightly negative effects for C/N ratios >100. Wu et al [34] observed that rapeseed cake with low C/N ratio showed high N 2 O emissions while wheat straw with high C/N ratio showed lower cumulative N 2 O emissions from red soil. Muhammad et al [35] discussed that incorporation of plant residues enhanced N 2 O emissions and this enhancement was quantitatively dependent on C/N ratio of the residues, lower C/N ratio of the residues inducing higher concentration of dissolved organic carbon and larger amount of N 2 O emission.…”
Section: N 2 O Emissionsmentioning
confidence: 99%